Playful activities ; spelling learning ; French language ; fifth year of primary school - bouderhem, hadda; Kharchi , Lakhdar (El Omda in Linguistics and Discourse Analysis, 2023)
<section class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto [content-visibility:auto] supports-[content-visibility:auto]:[contain-intrinsic-size:auto_100lvh] R6Vx5W_threadScrollVars scroll-mb-[calc(var(--scroll-root-safe-area-inset-bottom,0px)+var(--thread-response-height))] scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:f253023a-9761-44df-8a81-534fd3bbc4e0-2" data-testid="conversation-turn-6" data-scroll-anchor="false" data-turn="assistant"><div class="text-base my-auto mx-auto pb-10 [--thread-content-margin:var(--thread-content-margin-xs,calc(var(--spacing)*4))] @w-sm/main:[--thread-content-margin:var(--thread-content-margin-sm,calc(var(--spacing)*6))] @w-lg/main:[--thread-content-margin:var(--thread-content-margin-lg,calc(var(--spacing)*16))] px-(--thread-content-margin)"><div class="[--thread-content-max-width:40rem] @w-lg/main:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="6d8f426e-b227-40e0-a5fd-ee4cb686b4ca" data-message-model-slug="gpt-5-5" data-turn-start-message="true"> This article emphasizes playful activities in the learning process. It aims to explain the primary objective of this pedagogical approach which, if implemented methodically, can facilitate the learning of spelling. The main purpose of integrating play into spelling instruction is to help young learners use the foreign language both orally and in writing. In the Algerian school context, this can be achieved through various games and interactive activities. To validate our hypothesis, we propose strategies that promote observation, motivation, analysis, and memorization, while encouraging learners to experience the pleasure of learning, reading, and writing.